The Demographics of Citizen Science Participation and Its Implications for Data Quality and Environmental Justice. (7th October 2020) - Blake, Charlie; Rhanor, Allison; Pajic, Cody
Citizen science programs have been growing in popularity in recent years and can provide various benefits to participants and their communities. We sought to determine whether these benefits are equitably accessible to all by examining potential demographic disparities in participation in our statewide citizen science program. We first explored whether Illinois RiverWatch participants are demographically and geographically representative of Illinois's population. We conducted online surveys of current participants to gather information on demographics, including race, income, and education level, and then compared these responses with the population of Illinois as a whole using (US) census data. We also examined whether RiverWatch stream sites are disproportionately located in areas of low environmental justice concern, as determined by the US Environmental Protection Agency's (US EPA's) Environmental Justice screening tool. We used GIS to map all stream sites (n = 936) and determined whether they were located in areas of high or low environmental justice concern. The survey data indicate that RiverWatch participants are disproportionately white, highly educated, and affluent compared with the Illinois general population. In addition, we found RiverWatch sites tend to be located in areas of lower environmental justice concern, and that areas of high environmental justice concern are underrepresented. We discuss how disparities in demographics of participants can not only indicate need for improvement in the accessibility of a citizen science program but could also harm the quality of the river-monitoring data collected, as it leads to sampling that is not accurately representative.